2011
DOI: 10.1007/s00296-011-1796-z
|View full text |Cite
|
Sign up to set email alerts
|

The CD226 gene in susceptibility of rheumatoid arthritis in the Chinese Han population

Abstract: Recent case-control studies have identified some loci that are associated with rheumatoid arthritis (RA). Among these, a single nucleotide polymorphism (SNP), Gly307Ser (rs763361), in the CD226 gene was first discovered to confer the risk of RA in populations with European and Colombian ancestry. Because the effect of genetic factors varies in different races, the association between RA and CD226 is yet to be evaluated in other non-European populations. Here, we report the significant association between CD226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Four articles were excluded because 2 were review articles, 1 contained duplicate data, and 1 had no data concerning the polymorphisms. Thus, 19 studies met our inclusion criteria [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. They consisted of 8 studies on the CTLA-4 polymorphism with 2093 patients and 2480 controls, 5 on the CD226 polymorphism with 2278 patients and 1940 controls, 6 on the FAS polymorphism with 546 patients and 618 controls, and 3 on the FASL polymorphism with 321 patients and 307 controls (Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Four articles were excluded because 2 were review articles, 1 contained duplicate data, and 1 had no data concerning the polymorphisms. Thus, 19 studies met our inclusion criteria [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. They consisted of 8 studies on the CTLA-4 polymorphism with 2093 patients and 2480 controls, 5 on the CD226 polymorphism with 2278 patients and 1940 controls, 6 on the FAS polymorphism with 546 patients and 618 controls, and 3 on the FASL polymorphism with 321 patients and 307 controls (Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…While some studies have found that CTLA-4 rs5742909, CD226 rs763361, FAS-670 rs1800682, and FASL rs763110 polymorphisms are associated with RA, other studies have reported no such association [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. To overcome the limitations of individual studies, resolve inconsistencies, and reduce the likelihood that random errors are responsible for false positive or false negative associations [32][33][34], we performed a meta-analysis to determine whether these polymorphisms are associated with RA susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Many genes have been studied in this context, and the CD226 gene is one such gene in the context of autoimmune diseases. [9][10][11][12][13][14][15][16][17][18] Furthermore, accumulating evidence suggests the presence of common genetic factors that predispose to autoimmunity. The finding that the CD226 gene is associated with a subgroup of autoimmune diseases provides support for the notion that susceptibility to many autoimmune diseases may have some common susceptibility alleles or pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][35][36][37] Four reports were excluded due to a lack of genotype data, 8,[35][36][37] and thus, 10 reports met the inclusion criteria. [9][10][11][12][13][14][15][16][17][18] In addition, one of these reports contained data on two different groups, 13 and another on seven different groups, 9 and we analysed these studies independently. Therefore, a total of 17 separate studies were considered in the meta-analysis, which in total, contained 8900 patients and 10,295 controls, and seven European, five Asian and five South American sample populations (Table 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation